EMPOWERING WOMEN FARMERS THROUGHT MULTICHANNEL LEARNING: AN APPLICATION OF NEED ASSESSMENT TECHNIQUE - Fawzia Sulaiman (Indonesian Journal of Agricultural Science, 2000)
The suitability and effectiveness of material, method, and media used in nonformal education provided by government and nongovernment institutions (including agricultural extension) has been questioned in recent years, this is especially true for nonformal education catering for poor women farmers. Even though the significant roles and contribution of woman farmers in farming and family economic survival in Indonesia have been widely known, their nonformal educations need are rarely acknowledged. Several socio-cultural norms and values hinder women farmers’ participation in extension activities. The perception that agricultural extension activities fall under public domain has resulted that these activities are under male control (usually head for household). Without special intervention and accurate need assessment for nonformal education, the gap between women farmers and their male counterparts will be wider. This study was designed to identify nonformal educational needs of poor women farmers in Sakra Subdistrict, East Lombok, West Nusa Tenggara. The primary data and information were solicited through the Participatory Rural Appraisal (PRA) method using focus group interviews and gender analysis techniques. The result indicated that women farmers in the study area could not afford to participate in learning activities, unless the learning program offer a direct benefit to generate income. However, in general they put a high expectation in their children’s education and learning opportunity that would lead them to earn a better income. Due to their very limited educational background, demonstration and learning by doing method where perceived to be the most effective extension methods. Furthermore, radio and television were not effective educational channels, since there were only a very small number of respondents who owned radio and TV sets. In the efforts to empower women farmers, field extension workers require training on socio-economics, including gender analysis, and need assessment methodology to better perform their tasks in the field.